2019
DOI: 10.24980/ucsb.v2i4.3310
|View full text |Cite
|
Sign up to set email alerts
|

Frequência De Micronúcleos Em Etilistas

Abstract: O álcool etílico é um dos principais agentes químicos relacionados ao desenvolvimento de neoplasias malignas bucais. O uso do etanol tem aumentado em diversas populações e a faixa etária dos indivíduos que o consomem tem ficado cada vez mais baixa. O teste de micronúcleos é apontado como uma ferramenta importante na ação preventiva de carcinogênese e a quantificação da sua frequência representa um instrumento útil no monitoramento de indivíduos expostos a agentes genotóxicos de natureza ocupacional ou ambienta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
1
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
0
1
2
Order By: Relevance
“…Ambroise et al (2013) related the association of these factors and viral infections with the presence of this nuclear abnormalities and our results disagree with those presented by Wojda et al (2007), Kažimírová et al (2009), Nefic and Handzic (2013) and Franzke et al (2020), as they relate that increasing age associates to chromosomal instability and, consequently, promotes the formation of nuclear abnormalities, including MN. In our study, samples from patients who reported not drinking alcohol had a higher frequency of these chromosomal fragmentations and this association disagree of results pointed out by Dickemann et al (2018), who related absence of association between frequency of MN in oral mucosa cells of individuals exposed to mouthwashes containing alcohol. The discrepant results found can be explained by the low number of samples included in our study.…”
Section: Discussioncontrasting
confidence: 99%
“…Ambroise et al (2013) related the association of these factors and viral infections with the presence of this nuclear abnormalities and our results disagree with those presented by Wojda et al (2007), Kažimírová et al (2009), Nefic and Handzic (2013) and Franzke et al (2020), as they relate that increasing age associates to chromosomal instability and, consequently, promotes the formation of nuclear abnormalities, including MN. In our study, samples from patients who reported not drinking alcohol had a higher frequency of these chromosomal fragmentations and this association disagree of results pointed out by Dickemann et al (2018), who related absence of association between frequency of MN in oral mucosa cells of individuals exposed to mouthwashes containing alcohol. The discrepant results found can be explained by the low number of samples included in our study.…”
Section: Discussioncontrasting
confidence: 99%
“…Estudos vêm mostrando que agentes externos, como a exposição a pesticidas e radiação, uso de algumas drogas, álcool e cigarro, podem causar efeitos genotóxicos no DNA (SILVA et al, 2019;BALLESTRERI, 2017;MATHEUS LOBO;BOLAÑOS, 2014;ARALDI et al, 2013). O aparecimento de micronúcleos é uma das formas de adaptação do organismo para evitar maiores danos (DICKEMANN et al, 2018).…”
Section: Palavrasunclassified
“…Consistem em fragmentos de cromossomos (ou cromossomos inteiros) que não foram mantidos no núcleo após a divisão celular e formam uma estrutura externa ao núcleo principal de uma célula (COSTA JÚNIOR et al, 2018;GEUS et al, 2018). A formação dos micronúcleos pode ocorrer por ações de agentes endógenos ou exógenos (DICKEMANN et al, 2018).…”
Section: Introductionunclassified